2011
DOI: 10.1103/physrevb.84.024106
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of elastic properties of Cr- and Fe-rich Fe-Cr alloys

Abstract: Elastic properties of substitutionally disordered Cr-and Fe-rich Fe-Cr alloys are derived from first-principles calculations using the exact muffin-tin orbitals method and the coherent potential approximation. A peculiarity in the concentration dependence of elastic constants in Fe-rich alloys is demonstrated and related to a change in the Fermi surface topology. Our calculations predict high values for the elastic constants of Cr-rich Fe-Cr alloys, but at the same time show that these alloys could be rather b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 58 publications
6
24
0
Order By: Relevance
“…We use the generalized gradient approximation of Perdew and Wang [14] and projected augmented wave potentials [15]. We found that a plane wave energy cutoff of 350 eV is large enough for all metal systems to ensure the total energy and stress convergence, consistent with previous calculations [6,11,[16][17][18][19][20]. The Brillouin zone sampling was performed using the Monkhorst-Pack scheme [21], with 6 × 6 × 6 k-point meshes for a 32 atom supercell in fcc metals and 5 × 5 × 5 k-point meshes for a 54 atom supercell in bcc metals.…”
supporting
confidence: 58%
“…We use the generalized gradient approximation of Perdew and Wang [14] and projected augmented wave potentials [15]. We found that a plane wave energy cutoff of 350 eV is large enough for all metal systems to ensure the total energy and stress convergence, consistent with previous calculations [6,11,[16][17][18][19][20]. The Brillouin zone sampling was performed using the Monkhorst-Pack scheme [21], with 6 × 6 × 6 k-point meshes for a 32 atom supercell in fcc metals and 5 × 5 × 5 k-point meshes for a 54 atom supercell in bcc metals.…”
supporting
confidence: 58%
“…Moreover, elastic lattice strain induced by semi-coherent precipitate–matrix interfaces is low enough to be negligible. Instead, the difference in shear moduli between the BCC precipitates and matrix is high (Δ G = G BCC – G matrix = 100–85 = 15 GPa, where G BCC is adopted from the data of a Cr−22 at% Fe alloy 51 , 52 and G matrix is a value selected between the shear modulus of CoCrFeNi 17 and that of CoCrNi 16 ). Therefore, modulus strengthening Δ σ ms , which should be the primary contribution to the strength increase, is given by 19 : where m is a constant and is equal to 0.85 for FCC-based alloys.…”
Section: Methodsmentioning
confidence: 99%
“…However, the misfit can be enhanced if intermixing between Fe and Cr layers at the Fe/Cr interface is considered. 38 The presence of intermixing at the Fe/Cr interface has been suggested in previous studies. 39 To clarify this issue, the elemental composition of MgO/Fe/Cr/MgO with an Fe thickness of 1.5 nm and an MgO thickness of 3 nm was studied by electron energy loss spectroscopy (EELS).…”
Section: Resultsmentioning
confidence: 59%